2021
DOI: 10.1111/sltb.12667
|View full text |Cite
|
Sign up to set email alerts
|

Considerations in the assessment of help‐seeking and mental health service use in suicide prevention research

Abstract: ObjectiveThe connection of individuals at elevated suicide risk to mental healthcare services represents a critical component of suicide prevention efforts. This article provides recommendations for enhancing the assessment of help‐seeking and mental health service use within the context of suicide prevention research.MethodWe discuss evidence‐based and theoretical rationale for improving current approaches to assessing help‐seeking and mental health service use among at‐risk individuals.ResultsRecommendations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This patient population is a necessary stakeholder in suicide prevention and intervention development and policy discussions affecting mental health care. For example, our qualitative results elucidate how previous mental health care experiences and intersecting stigma affect SGM individuals’ desire and efforts to engage in mental health care, an important research target for suicide prevention research (Hom & Stanley, 2021). Future research should continue to engage SGM individuals with high suicide risk to explore help-seeking processes in more detail, particularly given how stigma can occur in early stages of help-seeking such as searching online for a provider (Holt et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This patient population is a necessary stakeholder in suicide prevention and intervention development and policy discussions affecting mental health care. For example, our qualitative results elucidate how previous mental health care experiences and intersecting stigma affect SGM individuals’ desire and efforts to engage in mental health care, an important research target for suicide prevention research (Hom & Stanley, 2021). Future research should continue to engage SGM individuals with high suicide risk to explore help-seeking processes in more detail, particularly given how stigma can occur in early stages of help-seeking such as searching online for a provider (Holt et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, our participants represent a varied sample of SGM adults including diversity in racial and ethnic identity, gender identity, sexual orientation, and geographic location. Future research should utilize qualitative methods to inquire specifically about how SGM adult survivors of suicide take steps toward engaging in mental health care to better inform suicide prevention efforts (Hom & Stanley, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The problem of conflicting ideals and reality, difficulty choosing and adapting to new learning environments and tasks, and various other psychological problems [4]. Universities have established student mental health management institutions such as mental health counseling centers and mental health consultation centers, aiming to care for students' mental health seriously, carefully counsel them on their psychological problems, scientifically diagnose their psychological diseases, and avoid the occurrence of their psychological problem crises [5][6]. Its main form is to map students' mental health problems, identify problems, and initiate psychological education classes such as lectures, mainly by distributing mental health questionnaires and analyzing them statistically [7][8][9].…”
Section: Background Of the Studymentioning
confidence: 99%
“…Studies have consistently shown that a significant proportion of individuals at high risk of suicide do not interact with mental health services (Hom and Stanley 2021). Limited health literacy has been associated with a variety of adverse health outcomes, such as increased rates of chronic disease, decrease in the use of health services, increased health care costs, and premature death (Crowe, Mullen, and Littlewood 2018).…”
Section: Introductionmentioning
confidence: 99%